2016
DOI: 10.1186/s13071-016-1304-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey of Enterocytozoon bieneusi in sheep and goats in China

Abstract: BackgroundOver recent years, several studies have conducted genotyping of Enterocytozoon bieneusi in various hosts worldwide using sequence analysis of the ribosomal internal transcribed spacer (ITS), however, relatively little is known about E. bieneusi in sheep and goats in China. Therefore this research was conducted to understand the prevalence and genotype distribution of E. bieneusi in farmed sheep and goats in China.ResultsA total of 1025 fecal specimens from farmed animals in various geographic areas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 50 publications
11
48
1
Order By: Relevance
“…Known and new genotypes are indicated by hollow and filled triangle, respectively. horses and wild boars Qi et al 2016;Shi et al 2016), CHC5 isolates have been found in dairy cattle and wild boar . This study shows the capacity of CHG19 and CHC5 isolates to adapt to different pig breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Known and new genotypes are indicated by hollow and filled triangle, respectively. horses and wild boars Qi et al 2016;Shi et al 2016), CHC5 isolates have been found in dairy cattle and wild boar . This study shows the capacity of CHG19 and CHC5 isolates to adapt to different pig breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of genotype MJ14 (HNR-VI) in pigs and rodents in the same province not only suggests that the genotype has an extensive host range, but that potential cross-species transmission between pigs and rodents can occur. Genotype CHG19 has been identified in pigs from Henan [48] and Shaanxi [49], in captive Eurasian wild boars from Sichuan [21], in goats from Yunnan [42], in horses from Xinjiang [32] and on the surfaces of vegetables and fruits from Henan [23]. This suggests that CHG19 has the ability to infect a large variety of animals.…”
Section: Genotypesmentioning
confidence: 98%
“…A large variety of animals have been reported to be infected with genotype EbpA. In addition to pigs, EbpA has been detected in non-human primates [37,39], cattle [5,6,11,58], sheep [42], goats [42,59], deer [54], horses [32,45], house mice [36], and birds [15,16], with a wide host range. This genotype has also been found in humans from the Czech Republic [38], Nigeria [2], and China [47], highlighting its zoonotic nature.…”
Section: Genotypesmentioning
confidence: 99%
“…To date, there have been nine reports on the identification and genotyping of E. bieneusi in goats [1,3,4,14,16,18,21,22,28]. In this study, the prevalence of E. bieneusi in black goats was 24.0% (82/341) which was lower than that in Chongqing (62.5%; 5/8) [21] and Henan (31.2%; 186/596) [14,18,21], but higher than that in Anhui (5.1%; 33/654) [14,21], Yunnan (12.8%; 60/470) [4,21], Jiangsu (2.7%; 2/74) [14], Heilongjiang (21.8%; 12/55) [28], Shaanxi (19.9%; 72/361) [18,21] and Tibet (9.6%; 25/260) [3]. Elsewhere, infection rates of 14.3% (1/7), 13.3% (11/83), and 19.2% (14/73) have been reported in goats from Spain [16], Egypt [1] and Thailand [22], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies of E. bieneusi have been performed in goats, particularly those in China [1,3,4,14,16,18,21,22,28]. A total of 46 ITS genotypes of E. bieneusi have been identified in goats, 11 of which have been detected in humans [1,3,4,13,14,16,18,21,22,28]. Nevertheless, the genotypes of E. bieneusi in goats in China are not fully understood.…”
Section: Introductionmentioning
confidence: 99%